Protective Effects of Bromelain in Testicular Torsion-Detorsion: Reducing Inflammation, Oxidative Stress, and Apoptosis While Enhancing Sperm Quality - Yakut, Seda; Karabulut, Merve; Koca, Recep Hakki; Erbas, Elif; Ozkanlar, Seckin; Gencer, Berrin Tarakci; Kumar, K. J. Senthil (Mdpi, 2025)
Inflammation and increased oxidative stress in testicular tissue are documented side effects of torsion of the testicles. The preventive role of Bromelain (Bro) against testicle torsion-induced ischemia/reperfusion (I/R) injury was investigated in this research. Five groups of six animals each were created: ischemia, Ischemia+Reperfusion (I+R), Ischemia+Reperfusion+Bromelain (I+R+Bro; 10 mg/kg), control (sham), and Bromelain (Bro; 10 mg/kg). An I/R damage resulted from two hours of 720 degrees clockwise twisting of the left testis. Blood samples and epididymal sperm were collected after reperfusion to analyze sperm parameters (recovery, motility, viability, and morphology) and cytokines that promote inflammation (IL-1 beta, IL-6, and TNF-alpha). Using Western blotting, testicular tissue was examined for histopathological alterations, antioxidant enzymes (GSH, SOD), lipid peroxidation (MDA), apoptosis, and survival-related proteins (TLR4, Caspase-3, Bcl-2, NRF-2, HO-1, PI3K, mTOR, AKT-1). While raising the activities of GSH and SOD, two antioxidant enzymes, Bro administration dramatically reduced MDA concentrations. The I+R+Bro group had significantly reduced amounts of cytokines that promoted inflammation compared to the I+R group. Bro's protective properties are also attributed to proteins that are altered by it and participate in the apoptosis and survival of cells. Sperm morphology, motility, and concentration notably improved in the bromelain-treated group, according to spermatological examination. Testicular samples treated with bromelain showed less tissue damage according to histological evaluations than the untreated I+R group. These findings imply that Bro has anti-inflammatory, anti-apoptotic, and antioxidant qualities. It effectively reduces oxidative stress and inflammation by modulating the PI3K/Akt/mTOR and NRF-2/HO-1 pathways, hence minimizing I/R injury.
Keywords: Bromelain; testicular torsion; ischemia/reperfusion injury; NRF-2/HO-1; PI3K/Akt/mTOR; apoptosis